Teachers’ experiences on the university inclusion of students with disabilities - Lévano Castro, Sofía (2026)
University-level educational inclusion of persons with disabilities continues to face challenges, despite the existence of regulatory frameworks that emphasize the need for appropriate accommodations. In practice, each university manages inclusion differently, often placing the responsibility on individual instructors who must navigate challenges for which they are not adequately trained. To explore how translation instructors experience educational inclusion at the university level, a phenomenological design was employed to understand their conceptualizations of inclusion, lived experiences, challenges faced, accommodations made, and perceptions of institutional support. The findings reveal heterogeneous perspectives on university inclusion, highlight the lack of institutional backing for meaningful inclusion, and underscore instructors’ willingness to support students with disabilities.